A multi-sectoral community development intervention has a positive impact on diet quality and growth in school-age children in rural Nepal - Miller, Laurie C.; Neupane, Sumanta; Joshi, Neena; Lohani, Mahendra (Wiley, 2024)
Poor diet quality (diet diversity and animal-source food [ASF] consumption) during childhood negatively affects growth, development, behaviour and physiologic function in later life. Relatively less is known about the impact of poor diet on the growth of school-age children compared to children <5 years of age, especially in low/middle-income countries. A better understanding of delivery strategies for effective interventions to improve diet and hence growth in school-age children is needed. A 36-month longitudinal controlled impact evaluation in rural Nepal assessed the nutrition and growth of children <5 years of age in families assigned via community clusters to full package intervention (community development, training in nutrition [during pregnancy and for children <5 years] and livestock husbandry), partial package (training only) or control (no inputs). Concurrent data were collected prospectively (baseline plus additional four rounds) on school-age children (5–8 years at baseline) in these households; the present study analysed findings in the cohort of school-age children seen at all five study visits (n = 341). Diet quality improved more in the full package school-age children compared to those in partial package or control households. full package children consumed more ASF (β +0.40 [CI 0.07,0.73], p < 0.05), more diverse diets (β +0.93 [CI 0.55,1.31], p < 0.001) and had better head circumference z-scores (β +0.21 [CI 0.07,0.35], p < 0.01) than control children. In conclusion, a multi-sectoral community development intervention was associated with improvements in diet and growth of school-age children in rural Nepal even though the intervention focused on the diet of children <5 years of age. The diet and growth of school-age children can be favourably influenced by community-level interventions, even indirectly.